Lipid Lowering Therapy with Combination of Niacin and Statin in Women: Age-Related Endothelial Effects. (28th December 2013) - Parker, Beth; Kothawade, Kamlesh; Kim, Namee; Paul-Labrador, Maura; Bairey Merz, Noel; Polk, Donna
Abstract : Background . Many women remain at risk for cardiac events despite treatment to reduce low-density lipoprotein cholesterol (LDL-C). We hypothesized that for postmenopausal women treated with niacin in addition to statin vascular function will improve. Methods . We conducted a randomized, double-blind, placebo-controlled trial of 16 weeks of niacin (N) versus placebo (PL) in 43 women (mean age, 67 ± 9 years) previously on statin therapy. Study outcomes included lipoprotein levels, vascular inflammation assessed by high sensitivity C-reactive protein (hsCRP), interleukin 6 (IL-6), tumor necrosis factor α (TNF- α ), and endothelial function, assessed as brachial artery flow mediated dilation (FMD). Results . The N group significantly increased HDL-C and decreased LDL-C cholesterol relative to PL (both P < 0.01 ). FMD improved in both groups (P = 0. 02 ) irrespective of niacin (P = 0.21 ). Age influenced change in FMD (P = 0.01 ) such that improved FMD (before to after) with lipid lowering therapy was greater with older age (P = 0.03 Pearson correlation = 0.34), independent of treatment group. Conclusions . Lipid lowering therapy with combination of niacin and statin does not improve inflammation or endothelial function compared to statin alone. However, older women demonstrate relatively greater endothelial benefit of lipid lowering therapy over 4 months. This trial is registered with Clinicaltrials.gov NCT00590629 .